2009
DOI: 10.1063/1.3234246
|View full text |Cite
|
Sign up to set email alerts
|

On the saturation in the average transmitted current in two-dimensional planar diodes

Abstract: The relation between average transmitted current density (JTR) and injected current density (JIN) in a two-dimensional planar diode is investigated using particle-in-cell simulation. Beyond the space charge limited value of injected current density, JTR is found to increase slowly with JIN and finally saturate for higher values. The physics of gradual increase in JTR to the saturation value is explained using the electric field profile at the cathode surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…For two-dimensional (2D) geometry, particle simulations by Luginsland et al, 8 and a simple theory by Lau, 9 have demonstrated that the 2D rearrangement of the equipotential profiles allows the extracted current to exceed the Child-Langmuir limit as the distance to the anode is increased. Further 2D simulations by Kumar and Biswas 10 have addressed the time-dependent behavior encountered for large injection currents. They also find that, on average, the transmitted currents can exceed the Child-Langmuir limit.…”
Section: Introductionmentioning
confidence: 99%
“…For two-dimensional (2D) geometry, particle simulations by Luginsland et al, 8 and a simple theory by Lau, 9 have demonstrated that the 2D rearrangement of the equipotential profiles allows the extracted current to exceed the Child-Langmuir limit as the distance to the anode is increased. Further 2D simulations by Kumar and Biswas 10 have addressed the time-dependent behavior encountered for large injection currents. They also find that, on average, the transmitted currents can exceed the Child-Langmuir limit.…”
Section: Introductionmentioning
confidence: 99%